Factors influencing career decision-making of senior secondary school students in Osun State (2013)
Despite all efforts at giving adequate training to Nigerian graduates, it is worrisome to note that instances of job inefficiency are on the increase, and job dissatisfaction continues unabated, while the zeal for occupational change among the workers did not stop. The study therefore investigated some of the factors influencing career decision-making of secondary school students in Osun State. Multistage sampling technique was employed to select 600 students from 12 secondary schools in Iwo federal constituency of the state. Four validated instruments were used to collect data, namely: Student Questionnaire on Self- Efficacy, Student Questionnaire on outcome expectation, Student Questionnaire on Family influence, and Student Career Questionnaire. Their reliability indices ranged from 0.63 to 0.86. The result of findings revealed that science students have the highest percentage of 55.7%, while Arts students have the lowest representation of 18.7%. There is strong relationship between career and self-efficacy (r=.822, p<.05); while outcome expectation showed low relationship with career (r =.128, P< .05). Family has no relationship with career (r= .040, P>.05). Self-efficacy, outcome expectation and family-influence had composite contribution to career decision-making. Self-efficacy and parental educational background were the most influential factors that contributed to career decision making of secondary school students. It was recommended that Government should appoint career counselors in schools who would assist students in discovering where their aptitude lie when career is to be chosen. Parents should not enforce any career on their children and career talk should be organized in schools before students register for external examinations.